Government of Travancore-Cochin the Second Five Year Plan Draft Part IV Description of Schemes - Planning Commission (Planning Commission, 1955)
Lemon Grass, which is a wild growth in the State, began to be grown as a commercial crop in recent years when the importance and value of lemon grass oil was recognised. It has now become one of the major cash crops of the State and is a very valuable dollar earner. The lemon grass oil produced in the State enjoys a very high reputation because of its high content of essential oils. Absolutely no research has been done on lemon grass cultivation in the State. It is understood that other countries are making head-way in raising the quality of lemon grass produced in those countries through improved agricultural and distillation practices. If we also do not evolve better processes of cultivation and distillation it is likely that we will soon be outstripped by competing countries. It has therefore been decided to do research work on lemon grass. A 25 acre farm is already in existence and the construction of a distillation shed, a field laboratory and a well for water supply will be completed in the First Five Year Plan period. The work in the Second Five Year Plan period will be mainly to make (a) Breeding and cultural studies through collection of varieties, single plant selections, isolation of pure strains, and fertiliser experiments; (b) distillation studies using different types of distilleries, the use of Crude oil and Furnace oil as fuel, and about the pre-treatment of grass; and (c) organisation of a producer’s Co-operative Society. The expenditure will be met jointly by the Government and the I.C.A.R. The scheme is expected to cost Rs. 1.22 lakhs.
Description of Schemes
Government of Travancore-Cochin